Mechanistic Insights into the Hot-Spot Formation and Pyrolysis of LLM-105 with Different Void Defects: A ReaxFF Molecular Dynamics Study - Mengyun Mei; Zijian Sun; Lixin Ye; Weihua Zhu (Molecules)
To investigate the influences of void defects of different sizes, molecular dynamics combined with ReaxFF-lg reactive force field was used to study the hot-spot formation mechanism and thermal decomposition behavior of 2,6-diamino-3,5-dinitropyrazine-1-oxide (LLM-105) crystals with different void defects at 2500 K. The results indicate that larger void defects are more conducive to the formation of hot-spots. The consistency of the trends in time evolution of the potential energy, species numbers, and small molecules amounts between the ideal and void-containing LLM-105 crystals demonstrates that the presence of the void defect does not alter the decomposition mechanism of the LLM-105 molecule. An increase in the size of the void defect significantly increases the degree of diffusion of the C, H, O, and N atoms in the crystals, which affects the effective collisions between the atoms and thus alters the occurrence frequency of relevant reactions and the production of relevant products.